Submarine Landslide Kinematics Derived From High‐Resolution Imaging in Port Valdez, Alaska. Issue 7 (11th July 2020) - Roland, Emily; Haeussler, Peter; Parsons, Tom; Hart, Patrick
Abstract: Submarine landslides caused by strong ground shaking during the M9.2 1964 Great Alaska earthquake generated a tsunami that destroyed much of the old town of Valdez, Alaska, and was responsible for 32 deaths at that location. We explore structural details of the 1964 landslide deposit, as well as landslide deposits from earlier events, in order to characterize kinematics of the landslide process. We present a new high‐resolution seismic reflection data set that images the 1964 landslide deposit and six pre‐1964 deposits with great detail. These deposits are represented by thick packages (~7–23 m) of debris within >500 m of fjord sedimentation above basement. Internal slide structures are associated with distinctive landslide failure mechanisms, including detailed erosional and depositional features and structures resolved within both landslide blocks and distal debris flow layers. Based on comparisons of deposit volume from subbottom structure and differenced bathymetry, we refine prior interpretations of the source of failed material. New data show evidence for basal erosion and reworking of fjord‐floor sedimentation. Additionally, material comprising the 1964 landslide appears to have been translated and deformed by lateral thrusting, rather than having been sourced entirely from upslope evacuation zones. Taking into account these complexities in depositional patterns, we show variations in slide size through Holocene time and relate the history of landslides to the paleoseismic record. Collectively, these new observations demonstrate that Port Valdez has a repeated history of large submarine landslides, which are likely associated with large megathrust earthquakes. Plain Language Summary: In Alaska fjords, local tsunamis have caused significant damage and loss of life when they are generated by landslides, often triggered by large earthquakes. In this study, we explore the record of past submarine landslide events in the Port Valdez fjord, which was the location of a deadly tsunami triggered by the 1964 Great Alaska earthquake. New subbottom data are used to characterize the most recent landslide deposit from 1964 that blankets the fjord floor, as well as older landslide deposits below the fjord floor that are likely associated with past earthquake‐triggered slide events. Images of these deposits obtained from seismic reflection methods help us to infer the processes of translation and deformation of material that occurred during the landslide, physical properties of the material that failed during the slide, and the size of past events. Characterizing the type of sediment transport processes, as well as the size and source of slides in Port Valdez, is important, as it should help us to better understand the process by which local tsunamis are generated in fjord settings and geohazards in Alaska and along other active margins. Key Points: High‐resolution seismic reflection data image seven submarine landslide debris deposits in great detail within the Port Valdez fjord New data provide information on landslide source, mechanisms of sediment transport, and the size of slide debris associated with past events The record of repeat landsides in Port Valdez correlates with large earthquakes and should inform earthquake and tsunami hazard models